Cosyntropin Attenuates Neuroinflammation in a Mouse Model of Traumatic Brain Injury - Siebold, Lorraine; Krueger, Amy C.; Abdala, Jonathan A.; Figueroa, Johnny D.; Bartnik-Olson, Brenda; Holshouser, Barbara; Wilson, Christopher G.; Ashwal, Stephen (Frontiers in Molecular Neuroscience, 2020)
Aim: Traumatic brain injury (TBI) is a leading cause of mortality/morbidity and is associated with chronic neuroinflammation. Melanocortin receptor agonists including adrenocorticotropic hormone (ACTH) ameliorate inflammation and provide a novel therapeutic approach. We examined the effect of long-acting cosyntropin (CoSyn), a synthetic ACTH analog, on the early inflammatory response and functional outcome following experimental TBI. Methods: The controlled cortical impact model was used to induce TBI in mice. Mice were assigned to injury and treatment protocols resulting in four experimental groups including sham + saline, sham + CoSyn, TBI + saline and TBI + CoSyn. Treatment was administered subcutaneously 3 hrs post injury and daily injections were given for up to seven days post injury. Early inflammatory response was evaluated at three days post injury through evaluation of cytokine expression (IL1β and TNFα) and immune cell response. Quantification of immune cell response included cell counts of microglia/macrophages (Iba1+ cells) and neutrophils (MPO+ cells) in cortex and hippocampus. Behavioral testing (n=10-14 animals/group) included open field and novel object recognition during the first week following injury and Morris water maze at 10-15 days post injury. Results: Immune cell quantification showed decreased accumulation of Iba1+ cells in the perilesional cortex and CA1 region of the hippocampus for CoSyn-treated TBI animals compared to saline-treated. Reduced numbers of MPO+ cells were also found in the perilesional cortex and hippocampus in CoSyn treated TBI mice compared to their saline treated counterparts. Furthermore, CoSyn treatment reduced IL1β expression in the cortex of TBI mice. Behavioral testing showed a treatment effect of CoSyn for novel object recognition with CoSyn increasing the discrimination ratio in both TBI and Sham groups, indicating increased memory performance. CoSyn also decreased latency to find platform during the early training period of the Morris water maze when comparing CoSyn to saline-treated TBI mice suggesting moderate improvements in spatial memory following CoSyn treatment. Conclusion: Reduced microglia/macrophage accumulation and neutrophil infiltration in conjunction with moderate improvements in spatial learning in our CoSyn treated TBI mice suggests a beneficial anti-inflammatory effect of CoSyn following TBI.